Genotoxic Effects in Human Fibroblasts Exposed to Microwave Radiation. Issue 1 (July 2018) - Franchini, Valeria; Regalbuto, Elisa; De Amicis, Andrea; De Sanctis, Stefania; Di Cristofaro, Sara; Coluzzi, Elisa; Marinaccio, Jessica; Sgura, Antonella; Ceccuzzi, Silvio; Doria, Andrea; Gallerano, Gian Piero; Giovenale, Emilio; et al.
Abstract : Abstract: In the last decades, technological development has led to an increasing use of devices and systems based on microwave radiation. The increased employment of these devices has elicited questions about the potential long-term health consequences associated with microwave radiation exposure. From this perspective, biological effects of microwave radiation have been the focus of many studies, but the reported scientific data are unclear and contradictory. The aim of this study is to evaluate the potential genotoxic and cellular effects associated with in vitro exposure of human fetal and adult fibroblasts to microwave radiation at the frequency of 25 GHz. For this purpose, several genetic and biological end points were evaluated. Results obtained from comet assay, phosphorylation of H2AX histone, and antikinetochore antibody (CREST)-negative micronuclei frequency excluded direct DNA damage to human fetal and adult fibroblasts exposed to microwaves. No induction of apoptosis or changes in prosurvival signalling proteins were detected. Moreover, CREST analysis showed for both the cell lines an increase in the total number of micronuclei and centromere positive micronuclei in exposed samples, indicating aneuploidy induction due to chromosome loss.